Short-Wavelength Light-Blocking Eyeglasses Attenuate Symptoms of Eye Fatigue - Lin, Jonathan B.; Gerratt, Blair W.; Bassi, Carl J.; Apte, Rajendra S. (Investigative ophthalmology & visual science, 2017)
The purpose of this study was to determine whether subjects who wear short wavelength-blocking eyeglasses during computer tasks exhibit less visual fatigue and report fewer symptoms of visual discomfort than subjects wearing eyeglasses with clear lenses. A total of 36 healthy subjects (20 male; 16 female) was randomized to wearing no-block, low-blocking, or high-blocking eyeglasses while performing a 2-hour computer task. A masked grader measured critical flicker fusion frequency (CFF) as a metric of eye fatigue and evaluated symptoms of eye strain with a 15-item questionnaire before and after computer use. We found that the change in CFF after the computer task was significantly more positive (i.e., less eye fatigue) in the high-block versus the no-block (P = 0.027) and low-block (P = 0.008) groups. Moreover, random assignment to the high-block group but not to the low-block group predicted a more positive change in CFF (i.e., less eye fatigue) following the computer task (adjusted β = 2.310; P = 0.002). Additionally, subjects wearing high-blocking eyeglasses reported significantly less feeling pain around/inside the eye (P = 0.0063), less feeling that the eyes were heavy (P = 0.0189), and less feeling that the eyes were itchy (P = 0.0043) following the computer task, when compared to subjects not wearing high-blocking lenses. Our results support the hypothesis that short-wavelength light-blocking eyeglasses may reduce eye strain associated with computer use based on a physiologic correlate of eye fatigue and on subjects' reporting of symptoms typically associated with eye strain.